2017
DOI: 10.1159/000481709
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Rehabilitation

Abstract: An increasing number of patients are living with or surviving cancer due to improvements in detection and treatment. However, patients who survive cancer may experience functional disabilities that impact on health, quality of life and ability to work. For example, physical disorders may include fatigue, reduced muscle strength, cognitive dysfunction, paresthesia or nutrition problems, while mental symptoms may include anxiety, depression, fear of relapse or insomnia. Multidimensional oncological rehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The main goals of medical rehabilitation programs are improvement of the patient's medical condition, development of coping strategies and reintegration into social and working life with the ICF [20] serving as a conceptual basis. The resulting complexity of rehabilitation programs equally applies to the psychosomatic and cancer rehabilitation settings [23,24]. Although it has been indicated that staff education may impact patient outcomes (train-the-trainer in acute clinical settings) [16], we were not able to detect effects in multifactorial inpatient rehabilitation.…”
Section: Rehabilitation Research and Practicementioning
confidence: 64%
See 1 more Smart Citation
“…The main goals of medical rehabilitation programs are improvement of the patient's medical condition, development of coping strategies and reintegration into social and working life with the ICF [20] serving as a conceptual basis. The resulting complexity of rehabilitation programs equally applies to the psychosomatic and cancer rehabilitation settings [23,24]. Although it has been indicated that staff education may impact patient outcomes (train-the-trainer in acute clinical settings) [16], we were not able to detect effects in multifactorial inpatient rehabilitation.…”
Section: Rehabilitation Research and Practicementioning
confidence: 64%
“…Oncological rehabilitation on average lasts 3 weeks and is mostly initiated after completion of primary treatment. It comprises medical treatment, physical training, psychological support/therapy, and social counseling [23]. Psychosomatic rehabilitation on average lasts 5 weeks involving multilevel psychosomatic assessment and multimodal treatment.…”
Section: Rehabilitation Programs For Patients (Non Study-specific)mentioning
confidence: 99%
“…A valuable line of research is to explore possible additional therapeutic strategies that could reduce treatment toxicity. As the mechanisms leading to radiation-induced cognitive impairment are multifactorial, several strategies, each addressing different mechanisms, have been proposed to potentially reduce the neurocognitive toxicity of radiation [69, 70]. For example, avoiding high-dose radiation on hippocampi and adding synthetic metallotexaphyrin motexafin gadolinium or memantine to WBRT have shown encouraging but mixed results [50, 51, 71-76].…”
Section: Discussionmentioning
confidence: 99%
“…Beside coping with the disease, the treatment of disease- and therapy-associated functional limitations and psychological consequences as well as the improvement of reduced physical functioning and health-related quality of life are important rehabilitation goals. 11 …”
Section: Introductionmentioning
confidence: 99%